The Pedagogic Grammarian's Dilemma: Modality and Personality in Grammatical Description - Berry, Roger (Studia Anglica Posnaniensia, 2009)
This paper investigates an issue that I call the "pedagogic grammarian's dilemma": the choice facing writers of pedagogic grammars between being specific about grammar and risking being wrong, or hedging and risking being vague, as formulated by Henry Widdowson (1997). Using two corpora of grammatical description, it examines how a number of exponents of modality are used to hedge and finds firstly that they are far more common than in ordinary text. More importantly there is a link between the use of such modality and the approach to personality chosen in the grammars: hedging is more common when the more friendly YOU is used to address users than when WE is used; this suggests an interpersonal (as well as epistemic) motivation for the hedging. Overall the response of the grammars studied to the pedagogic grammarian's dilemma is to hedge, in order, it seems, to avoid being prescriptive.